A comparison of methods to quantify cationization of cellulosic pulps. (4th March 2017) - Odabas, Nora; Amer, Hassan; Henniges, Ute; Potthast, Antje; Rosenau, Thomas
Abstract : Fibers resulting from pulping of wood are negatively charged by nature. This charge might be reversed by chemical modification for different applications. In this study, different options to determine the degree of substitution (DS) with cationic groups introduced using 2, 3-epoxypropyltrimethylammonium chloride, a common cationization reagent, are compared. Classical analytical methods for this purpose include elemental analysis, which is unspecific, and titration, which is sensitive toward impurities and highly elaborate. These are complemented by fast and robust approaches based on infrared spectroscopy or thermogravimetric analysis. The absorption increase at 1480 cm −1 is specific for the introduced R-NMe3 and linearly correlated with the DS. For bleached Kraft pulps, cationization splits the thermal degradation of cellulose in two phases, their ratio being roughly proportional to the DS. Both methods require virtually no sample preparation. Infrared spectroscopy is particularly easy to apply and allows a quantification of pulp cationization in short time.